2007
DOI: 10.1271/bbb.70472
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Hypolipidemic Effects of Diosgenin, a Steroidal Saponin of Yam (Dioscorea spp.), on High-Cholesterol Fed Rats

Abstract: Diosgenin (a steroidal saponin of yam) has long been used as a raw material for the industrial production of steroid drugs, and reported to have a hypocholesterolemic effect by suppressing cholesterol absorption and increasing cholesterol secretion. Oxidative stress has been suggested as a main risk factor in the development of atherosclerosis. The aim of this study is to investigate the possible hypolipidemic and antioxidative effect of diosgenin on rats fed with a high-cholesterol diet supplemented with eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(139 citation statements)
references
References 44 publications
3
133
0
3
Order By: Relevance
“…This means SALE supplementation alone was not enough to lower cholesterol content to below control. Compounds that play a role in lowering cholesterol might be alkaloids and non-alkaloids (Santoso et al, 2010), saponins (Son et al, 2007), polyphenol (Ngamukote et al, 2011;Zang et al, 2006), flavonoid (Shrime et al, 2011). Patil et al (2010) reported that the reduction of cholesterol and triglycerides by alkaloids were in part caused by the reduction of lipogenic enzymes activities and increased bile acid excretion in feces.…”
Section: Levels Of Fat Protein and Cholesterol Meatmentioning
confidence: 99%
“…This means SALE supplementation alone was not enough to lower cholesterol content to below control. Compounds that play a role in lowering cholesterol might be alkaloids and non-alkaloids (Santoso et al, 2010), saponins (Son et al, 2007), polyphenol (Ngamukote et al, 2011;Zang et al, 2006), flavonoid (Shrime et al, 2011). Patil et al (2010) reported that the reduction of cholesterol and triglycerides by alkaloids were in part caused by the reduction of lipogenic enzymes activities and increased bile acid excretion in feces.…”
Section: Levels Of Fat Protein and Cholesterol Meatmentioning
confidence: 99%
“…Coenzyme Q10 supplementation was associated with significant reduction in thiobarbituric acid reactive substances, malondealdehyde and diene conjugates in coronary artery disease patients, indicating an overall decrease in oxidative stress (Singh and Niaz, 1999). However, the relationship between oxidative stress and cholesterol levels was confirmed in many studies (Pappolla et al, 2002;Balkan et al, 2004;Chang et al, 2006;Son et al, 2007;Codoñer-Franch et al, 2008;Yao et al, 2008;Nakagami et al, 2009). Ramirez-Tortosa et al, (2008) investigated the effects of the administration of water soluble Coenzyme Q10 in the plasma and liver mitochondria of rabbits fed with a high-fat diet (3% lard + 1.3% cholesterol).…”
Section: Discussionmentioning
confidence: 97%
“…Diosgenin (a steroidal sponin of Dioscorea spp.) supplementation (0.5%) caused a 27% and 13% increase in GPx and CAT activities in erythrocytes of rats (Son et al, 2007).…”
Section: Effect On Antioxidant Activitymentioning
confidence: 89%